FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN BUMN DI KOTA PALEMBANG - Sirajuddin, Betri (Balance : Jurnal Akuntansi dan Bisnis, 2016)
Problem formulation in this study is are factors that affect (relevant factor, to be understood, power test, neutral, right time, power of appeals, and complete) partial and collectively. The goal influence factors relevant to know, can be understood, power test, neutral, right time, power of appeals, and the quality of complete financial statements on state-owned company in palembang good partial nor collectively. This study included research type associative. in the state-owned company conducted in palembang. Variables in this study is relevant, to be understood, power test, neutral, right time, power of appeals, and complete. data used data is a primary and secondary data. Techniques of data collection in this study using questionnaires and documentation techniques. analysis qualitative data was used.research shows that good partial nor collectively relevant factor, to be understood, power test, neutral, right time, power of appeals, and complete significantly impact on the quality of financial reports state-owned company in palembang.